Analysis Of Work Productivity Through Employee Training At PT. Pegadaian KCP Sumedang - Megah Dewi Anggini (Journal of Bussines Management Basic, 2022)
The focus of this research contains analysis of work productivity through employee training at PT. Pegadaian KCP Sumedang. The purpose of this study was to determine how work productivity through training and efforts to increase employee productivity at PT. Pegadaian KCP Sumedang. The background of this research is that employee productivity can continue to increase and develop with the existence of various training programs for both new employees and old employees, which are held both in-person and online training. In addition there is also education so that employees can master more than one field of work, so that when there is a rotation of positions the employees already know what job descriptions must be done. The method used in the research is descriptive qualitative with two variables, namely productivity and training. Data collection techniques used are observation, interviews, documentation, and triangulation. Using data analysis Miles and Huberman (1984) namely data reduction, data display and conclusion drawing. There are results and discussions in this study, namely the work productivity of employees at PT. Pegadaian KCP Sumedang has experienced an increase, although gradually. It can be seen through self-development and the quality of employees at work. Although there are a few shortcomings in its implementation, it does not become an obstacle but instead makes it a motivation to be able to continue to learn and develop. PT. Pegadaian held an ourding innovation, which is an activity specifically for employees to put forward ideas for both products and services. Various trainings carried out by employees at PT. Pegadaian KCP Sumedang include workshops, e-learning and sharia learning. Employees are equipped with motivation and various learnings, which make employees not only master one field of work but also master other fields of work.